ASSESSMENT OF THE NUTRITIONAL VALUE OF MARE'S MILK AND FERMENTED MARE'S MILK PRODUCTS AND THE POSSIBILITY OF THEIR USE IN BABY FOOD - Alexandr V. Yakunin; Yuriy A. Sinyavskiy; Ykylas S. Ibraimov ("Paediatrician" Publishers LLC, 2017)
Background. Mare's milk is a promising source for making baby food products.Objective. Our aim was to assess the nutritional value, fatty acid and ascorbic  acid content in mare's milk and its products  as well as the possibility of their use in baby food.Methods. Mare's milk and its products  - drinking milk, yogurt, fermented  milk product  and curds - are taken as targets of research.  The content of proteins, fats, carbohydrates and caloric content is determined in the products. The fatty acid composition is studied by gas chromatography,  the content of vitamin C - by high-performance  liquid chromatography.  When calculating the daily intake of dairy and fermented milk products for children aged 1-11 years, the recommendations of the Union of Pediatricians of Russia as well as the norms of physiological needs were used.Results.  It has been found that mare's milk products are energy-restricted.  Inclusion of mare's milk products in the diet of children aged 12-23 months will meet the need for omega-6 by 15-34%, for omega-3 by 15-23%, for vitamin C by 39.6-57.3% of the recommended  daily dose. For children aged 2-11 years, daily consumption of 200 ml of yogurt based on mare's milk provides a daily dose of omega-6 by 4.3-14.5%, of omega-3 by 6.4-12.0%, of vitamin C by 23.8-31.7% of the recommended daily dose. Conclusion. The study results indicate that it is advisable to include fermented mare's milk products in the diet of children aged 1-11 years.